2016
DOI: 10.3389/fpsyg.2016.01053
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Emotional, and Psychosocial Functioning of Girls Treated with Pharmacological Puberty Blockage for Idiopathic Central Precocious Puberty

Abstract: Central precocious puberty (CPP) develops due to premature activation of the hypothalamic-pituitary-gonadal (HPG) axis, resulting in early pubertal changes and rapid bone maturation. CPP is associated with lower adult height and increased risk for development of psychological problems. Standard treatment of CPP is based on postponement of pubertal development by blockade of the HPG axis with gonadotropin releasing hormone analogs (GnRHa) leading to abolition of gonadal sex hormones synthesis. Whereas the hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 56 publications
2
33
0
1
Order By: Relevance
“…A study of 15 girls with CPP and 15 age-matched controls reported the only detectable difference in a large battery of tests was that treated girls showed higher emotional reactivity on 1 of 2 tests. Overall, these authors concluded that treated CPP girls did not differ in their cognitive or psychological functioning from control girls [26]. In summary, with few studies, utilizing different patient selection criteria and reporting disparate prevalence of behavioral problems in CPP girls, it remains unclear if psychosocial stress should be considered a predictable consequence of early puberty supporting a decision to start GnRHa therapy, and if so, whether treatment relieves such stress.…”
Section: Do Girls With Cpp Have More Psychological Problems Than Prepmentioning
confidence: 99%
“…A study of 15 girls with CPP and 15 age-matched controls reported the only detectable difference in a large battery of tests was that treated girls showed higher emotional reactivity on 1 of 2 tests. Overall, these authors concluded that treated CPP girls did not differ in their cognitive or psychological functioning from control girls [26]. In summary, with few studies, utilizing different patient selection criteria and reporting disparate prevalence of behavioral problems in CPP girls, it remains unclear if psychosocial stress should be considered a predictable consequence of early puberty supporting a decision to start GnRHa therapy, and if so, whether treatment relieves such stress.…”
Section: Do Girls With Cpp Have More Psychological Problems Than Prepmentioning
confidence: 99%
“…Gonadotropin releasing hormone agonists (GnRHas) have been found to impair memory in adults, so the study by Wojniusz et al (2016) on the possible cognitive effects of these drugs on children treated for idiopathic central precocious puberty (CPP) represents an important contribution to research in this area. Recent findings that GnRHas increase depression symptoms (Macoveanu et al, 2016) and slow reaction time (Stenbæk et al, 2016) in healthy women, and reduce long-term spatial memory in sheep (Hough et al, 2017) underline the importance of the research that Wojniusz et al (2016) have undertaken.…”
mentioning
confidence: 99%
“…Recent findings that GnRHas increase depression symptoms (Macoveanu et al, 2016) and slow reaction time (Stenbæk et al, 2016) in healthy women, and reduce long-term spatial memory in sheep (Hough et al, 2017) underline the importance of the research that Wojniusz et al (2016) have undertaken. However, their reassuring statement in the abstract that girls undergoing GnRHa treatment for CPP and controls “showed very similar scores with regard to cognitive performance” and their conclusion that “GnRHa treated girls do not differ in their cognitive functioning … from the same age peers” (Wojniusz et al, 2016) may be overly optimistic. These statements minimize the fairly substantial difference found in IQ scores and may also overemphasize its lack of statistical significance, as given the small number of participants in the study statistical significance has a high threshold.…”
mentioning
confidence: 99%
See 2 more Smart Citations